The Impact of Arab Lobby on the US National Interests in the Middle East: The Case of Oil Supplies - RIENE, Radhia; SAI, Ouarda (University of Eloued جامعة الوادي, 2024)
This dissertation examines the impact of the Arab Lobby on U.S. national interests in the Middle East, with a specific focus on the case of oil supplies. The study seeks to analyse the strategies and influence of the Arab Lobby in shaping U.S. policies towards the Middle East, particularly in relation to the region's oil resources. This research employs qualitative research. It opts for historical and descriptive methods. The findings of this study shows that The Arab lobby, notably the Saudi lobby, influences U.S. oil policy through financial backing, lobbying efforts, and strategic alliances, as seen in the AWACS deal. Employing a multifaceted strategy, the Arab community influences U.S. interests in the Middle East by engaging in negotiations, utilising top lobbyists, and launching PR campaigns, exemplified in the Dubai Ports deal. Utilising diverse tactics such as grassroots mobilization and media campaigns, the Arab lobby aims to garner public and political support, enhance Arab states' image, and access policymakers to advance regional interests. تتناول هذه الأطروحة تأثير اللوبي العربي على المصالح الوطنية الأمريكية في الشرق الأوسط، مع التركيز بشكل خاص على حالة إمدادات النفط. تسعى الدراسة إلى تحليل استراتيجيات اللوبي العربي وتأثيره في تشكيل السياسات الأمريكية تجاه الشرق الأوسط، خاصة فيما يتعلق بموارد المنطقة النفطية. يستخدم هذا البحث النوعي. ويختار الأساليب التاريخية والوصفية. تظهر نتائج هذه الدراسة أن اللوبي العربي، وخاصة اللوبي السعودي، يؤثر على السياسة النفطية الأمريكية من خلال الدعم المالي، وجهود الضغط، والتحالفات الاستراتيجية، كما رأينا في صفقة الأواكس. ومن خلال استخدام استراتيجية متعددة الأوجه، تؤثر الكتلة العربية على مصالح الولايات المتحدة في الشرق الأوسط من خلال الانخراط في المفاوضات، والاستفادة من كبار جماعات الضغط، وإطلاق حملات العلاقات العامة، المتمثلة في صفقة موانئ دبي. ومن خلال استخدام تكتيكات متنوعة مثل التعبئة الشعبية والحملات الإعلامية، يهدف اللوبي العربي إلى حشد الدعم الشعبي والسياسي، وتعزيز صورة الدول العربية، والوصول إلى صانعي السياسات لتعزيز المصالح الإقليمية.
Literature and Civilization
Keywords: Arab Lobby; Energy Security; Foreign Policy; Middle East; Oil Supplies; U.S. National interests.; اللوبي العربي، المصالح الوطنية الأمريكية، الشرق الأوسط، إمدادات النفط، السياسة الخارجية، أمن الطاقة.